2017
DOI: 10.1186/s13020-017-0131-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bushen Tianjing Recipe in a rat model of tripterygium glycoside-induced premature ovarian failure

Abstract: BackgroundBushen Tianjing Recipe (BTR) is a traditional Chinese herbal medicine that has been prescribed for premature ovarian failure (POF) for decades in China. Nevertheless, little is known regarding its underlying molecular mechanism. In the present study, we investigated the effects of BTR in a tripterygium glycoside (TG)-induced-POF rat model.MethodsThree doses of BTR were administered via intragastric gavage to adult female Sprague–Dawley (SD) rats with TG-induced POF. After 15 days of treatment, the es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…The rats (7 rats/group) were intragastrically treated with control solution or one of three doses of quercetin (12.5 mg/kg, 25 mg/kg, and 50 mg/kg) for 90 days. After quercetin administration, estrous cycles of all rats (15 months old) stopped at either estrus (46.43%) or diestrus (53.57%) (Table 3 ), indicating that the estrous cycle had been terminated in all rats [ 17 ]. Furthermore, no obvious differences in the estrous cycle were observed between the control group and the groups treated with the three doses of quercetin, indicating that quercetin did not affect the estrous cycle of menopausal rats.…”
Section: Resultsmentioning
confidence: 99%
“…The rats (7 rats/group) were intragastrically treated with control solution or one of three doses of quercetin (12.5 mg/kg, 25 mg/kg, and 50 mg/kg) for 90 days. After quercetin administration, estrous cycles of all rats (15 months old) stopped at either estrus (46.43%) or diestrus (53.57%) (Table 3 ), indicating that the estrous cycle had been terminated in all rats [ 17 ]. Furthermore, no obvious differences in the estrous cycle were observed between the control group and the groups treated with the three doses of quercetin, indicating that quercetin did not affect the estrous cycle of menopausal rats.…”
Section: Resultsmentioning
confidence: 99%
“…Rats that went through at least two consecutive regular estrous cycles were included in the experiments. The length of an estrous cycle was determined as the number of days between two non-consecutive days during which estrus cytology was observed [25]. The average length of regular estrous cycles in the rats was 4.4 days ( n = 18), ranging from 4 to 5 days.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have suggested that the efficacy of MSC transplantation on POI is mainly attributed to the paracrine mechanism [9, 10]. MSCs can secrete a variety of paracrine/autocrine factors, including growth factors, chemokines, and colony-stimulating factors, which are called secretomes, that mediate diverse functions [2325]. Some studies have shown that the MSC secretome could be therapeutic for the treatment of diseases [2628].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speaking of which, management of POF in western medicine nowadays involves immunosuppressive treatment, hormone therapy such as hormone replacement therapy (HRT), and ovarian transplantation [ 13 , 14 ]. Immunosuppressive treatment presents possibility of resumption of ovarian function; nevertheless, treatment with immunosuppressive agents failed to reverse the course of the ovarian autoimmunity or enhance the ovarian response to gonadotropins [ 15 ].…”
Section: Introductionmentioning
confidence: 99%